Identities of Teacher Educators in Higher Education: A Literature Review - Leanete Thomas Dotta; Amélia Lopes (Universidad Pedagógica Nacional, 2023)
Within the research field on teacher educators there is an overwhelming array of perspectives, which requires meticulous organization and deeper analysis. The general goal of this article is to characterize research studies on teacher educators. More specifically, the article intends to identify the role played by the studies on teacher educators' identities in that broader context. A literature review covering almost two decades of publications was conducted. First, the authors identified the selected themes, their geographies and their evolution throughout time, revealing the importance of Professional Development, a topic which includes the subtopic of teacher educators' identities. The content analysis of the articles related to this subtopic made it possible to identify four dynamic fields: two related with teacher educators' biographies and roles; and the others, connected with both the broader and specific contexts of teacher educators' work.